2021
DOI: 10.2106/jbjs.oa.21.00040
|View full text |Cite
|
Sign up to set email alerts
|

Percutaneous Forefoot Decompression in a Foot Compartment Syndrome Model

Abstract: Background:Acute compartment syndrome of the foot is a controversial topic. Release of the foot has been seen as complicated because of large incisions and postoperative morbidity, and there has been debate over whether this procedure is actually effective for releasing all areas of increased pressure. New sensor technology affords the opportunity to advance our understanding of acute compartment syndrome of the foot and its treatment. The purpose of the present study was to determine whether percutaneous deco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…Work by the current authors 6 has shown that 4 compartments consistently exist in the medial and volar forefoot, with a fifth possible compartment being the more superficial lateral abductor minimi group. This has been validated on a series of cadaver ACS models using ultrasound, sequential compartment pressurization, and the use of multiple pressure monitors 6,7 to determine the presence of physiological compartments. Traditionally, wide surgical releases have been used to accomplish compartment release.…”
mentioning
confidence: 70%
See 3 more Smart Citations
“…Work by the current authors 6 has shown that 4 compartments consistently exist in the medial and volar forefoot, with a fifth possible compartment being the more superficial lateral abductor minimi group. This has been validated on a series of cadaver ACS models using ultrasound, sequential compartment pressurization, and the use of multiple pressure monitors 6,7 to determine the presence of physiological compartments. Traditionally, wide surgical releases have been used to accomplish compartment release.…”
mentioning
confidence: 70%
“…It is generally accepted that there is a lateral compartment, a superficial central compartment, a medial compartment (sometimes described as 2 compartments with a separate abductor), and an interosseous compartment (described as either 1 continuous compartment or 4 separate compartments) [3][4][5] . Work by the current authors 6 has shown that 4 compartments consistently exist in the medial and volar forefoot, with a fifth possible compartment being the more superficial lateral abductor minimi group. This has been validated on a series of cadaver ACS models using ultrasound, sequential compartment pressurization, and the use of multiple pressure monitors 6,7 to determine the presence of physiological compartments.…”
mentioning
confidence: 70%
See 2 more Smart Citations